(untitled) (Vietnam Journal of Community Medicine, 2022)
The study is aimed at describing the disease structure of Cham ethnic minority in the South Central Region. A cross-sectional study was conducted on 15.993 Cham people in Ninh Thuan, Binh Thuan, Binh Dinh and Phu Yen provinces from January 2020 to December 2020. Information on the current state of illness and disease of people was collected through medical examination and interviews by doctors, nurses, and technicians of Military Hospital 175. The results showed that the prevalence of symptoms of the disease in the past 1 month was 70.4%; the average number of disease symptoms was 3.7 disease symptoms/person. The prevalence of chronic disease was 68.3%; the average number of diseases was 2.1 diseases/person. Five chapters of diseases with the highest incidence were Chapter IV Endocrine, nutritional and metabolic diseases (31.2%); Chapter VII Diseases of the eye and adnexa (22.0%); Chapter IX Diseases of the circulatory system (21.6%); Chapter XIII Diseases of the musculoskeletal system and connective tissue (16.2%), and Chapter XI Diseases of the digestive system (16.0%). Ten diseases with the highest incidence were hypertension (20.2%), gastritis (10.3%), dental caries (9.3%), cataracts (8.7%), pterygium (8.2%), inflammation allergic rhinitis (5.5%), pharyngitis (5.5%), vestibular disorders (5.3%), refractive errors (4.7%), and arthritis (4.7%). The percentage of Cham people with chronic diseases was quite high, especially hypertension. It is necessary to strengthen meeting the needs and access to medical examination and treatment services of the Cham people.